2011
DOI: 10.1007/s12103-010-9084-0
|View full text |Cite
|
Sign up to set email alerts
|

Crime Control in the 2008 Presidential Election: Symbolic Politics or Tangible Policies?

Abstract: Presidential candidates regularly use crime issues to help win electoral support. Contrary to conventional wisdom, crime control became an issue in the 2008 presidential campaign. Despite decreasing crime rates and public opinion focused only temporarily on illegal immigration, the three major presidential candidates (Obama, Clinton, & McCain) discussed many anticrime initiatives during the campaign. Unlike past research which has found presidential candidates use primarily symbolic rhetoric in their anticrime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…The univariate data, however, demonstrated that the majority of speeches in presidential election years were not symbolic, but rather substantive. This may very well be for the fact that presidents feel they have to make campaign promises to communicate to the public what their agenda will be if elected president, so rather than engaging the public in symbolic rhetoric, they are more explicit in what they would do in all areas of policy making if elected (Marion & Farmer, 2003; Marion & Oliver, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The univariate data, however, demonstrated that the majority of speeches in presidential election years were not symbolic, but rather substantive. This may very well be for the fact that presidents feel they have to make campaign promises to communicate to the public what their agenda will be if elected president, so rather than engaging the public in symbolic rhetoric, they are more explicit in what they would do in all areas of policy making if elected (Marion & Farmer, 2003; Marion & Oliver, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As the latter has articulated, “the politicization of crime is frequently a symbolic exercise without serious policy intentions—particularly at the national level” (Scheingold, 1984, p. 181). Since then, there has been increased evidence that presidents engage in symbolic politics when it comes to their campaign speeches (Marion & Farmer, 2003; Marion & Oliver, 2011), executive orders (Oliver, 2001), and in their budgetary requests to Congress (Caldeira, 1983; Caldeira & Cowart, 1980; Oliver & Marion, 2006, 2009), which has the impact of influencing both the public and Congress. All of the research until recently, however, has been qualitative in nature, only recently has an attempt been made to explain when and why presidents employ symbolic rhetoric through the use of logistic regression (Marion & Oliver, 2013).…”
Section: Symbolic Rhetoric Presidents and Crime Policy Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Символические действия и выступления разъясняют публике сущность проблем и предлагаемых решений. Тем самым политики успокаивают обеспокоенных граждан и дают им понять, что избранное официальное лицо знает о проблеме, заботится о гражданах и что предпринимаются меры для решения проблемы [21][22][23]. Другими словами, они «убеждают и успокаивают общественность» [24, p. 13].…”
Section: демонстрация контроля над преступностью и моральная обеспокоunclassified
“…Yet, there is still reason to expect that Republicans may benefit electorally from the salience of the issue even when they face weakened trust on it. While the Democratic Party and its candidates have made appeals about crime throughout recent history (Marion & Oliver, 2012, 2013Marion, Smith, & Oliver, 2009;Oliver, 2002Oliver, , 2003aOliver, Hill, & Marion, 2011;Oliver & Marion, 2006, 2008Oliver et al, 2016), the likelihood for these actions to translate into electoral gains is far more tenuous for them than it is for their Republican counterparts. When first detailing issue ownership theory, Petrocik (1996) argued that Democratic action on crime has the potential to provoke distress among their strongest supporters.…”
Section: Republican Ownership Of the Crime Issue?mentioning
confidence: 99%